2022
DOI: 10.1007/s00213-022-06179-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of alcohol and co-witness information on memory reports: a field study

Abstract: Rationale Witnesses who discuss a crime together may report details that they did not see themselves but heard about from their co-witness. Co-witness information may have beneficial and harmful effects on memory accuracy depending on whether the information was correct or incorrect. Objectives Given the prevalence of intoxicated witnesses, it is imperative to understand how alcohol influences this effect. Methods T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(71 reference statements)
0
1
0
Order By: Relevance
“… Crossland et al (2020) , for example, showed that although intoxicated participants did not additionally benefit from receiving a well-conducted interview, all participants (intoxicated or not) did have more complete statements when a well conducted interview was applied. Apart from Jores et al’s meta-analysis, future meta-analyses might concentrate on other important practical aspects on how alcohol affects memory such as whether it might affect the reporting of suggested information or whether a Cognitive Interview might counteract the debilitating memory effects of alcohol (see also Bartlett et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“… Crossland et al (2020) , for example, showed that although intoxicated participants did not additionally benefit from receiving a well-conducted interview, all participants (intoxicated or not) did have more complete statements when a well conducted interview was applied. Apart from Jores et al’s meta-analysis, future meta-analyses might concentrate on other important practical aspects on how alcohol affects memory such as whether it might affect the reporting of suggested information or whether a Cognitive Interview might counteract the debilitating memory effects of alcohol (see also Bartlett et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%